Hubungan Pengetahuan dan Keterampilan dengan Perilaku Penggunaan APAR pada Pekerja Bagian Produksi di Perusahaan Otomotif Karawang - Siti Nur'awini Alliya Lestari Chandra Dewi Kusumaningrum; Bachtiar Chahyadhi; Hengky Ditya Eko Nugroho (Sekolah Vokasi, Universitas Sebelas Maret, 2025)
The company's fire accident report data in the last 5 years has 7 fire cases. The description of fire control shows that workers have different APAR usage behavior. The company has conducted fire extinguisher training once a year but not thoroughly so that the knowledge and skills of each worker are different. This study aimed to determine the relationship between knowledge and skills with fire extinguisher use behavior among production workers in Karawang automotive company. This type of research was analytic observational with a crosssectional approach. The population in this study were 105 production workers, then using a minimum sample with the Slovin formula, the sample size was 92 respondents. The sampling technique used simple random sampling technique. Measurement of knowledge and behavior using a questionnaire. Measurement of skills using a checklist. Somers'd test was used for bivariate analysis and ordinal logistic regression test for multivariate analysis. Somers'd test results between APAR knowledge and APAR use behavior (p = 0.0001), APAR use skills with APAR use behavior (p = 0.0001). The results of the ordinal logistic regression test show that APAR knowledge has the most significant relationship with a p value = 0.0001 and t = 37.759.